Dark energy as a kinematic effect - Jennen, Hendrik [UNESP] (2016)
Observations during the last three decades have confirmed thatthe universe momentarily expands at an accelerated rate, which is assumed to be driven by dark energy whose origin remains unknown. The minimal manner of modelling dark energy is to include a positive cosmological constant in Einstein's equations, whose solution in vacuum is de Sitter space. This indicates that the large-scale kinematics of spacetime is approximated by the de Sitter group SO(1,4) rather than the Poincaré group ISO(1,3). In this thesis we take this consideration to heart and conjecture that the group governing the local kinematics of physics is the de Sitter group, so that the amount to which it is a deformation of the Poincaré group depends pointwise on the value of a nonconstant cosmological function. With the objective of constructing such a framework we study the Cartan geometry in which the model Klein space is at each point a de Sitter space for which the combined set of pseudoradii forms a nonconstant function on spacetime. We find that the torsion receives a contribution that is not present for a cosmological constant. Invoking the theory of nonlinear realizations we extend the class of symmetries from the Lorentz group SO(1,3) to the enclosing de Sitter group. Subsequently, we find that the geometric structure of teleparallel gravity--- a description for the gravitational interaction physically equivalent to general relativity--- is a nonlinear Riemann--Cartan geometry.This finally inspires us to build on top of a de Sitter--Cartan geometry with a cosmological function a generalization of teleparallel gravity that is consistent with a kinematics locally regulated by the de Sitter group. The cosmological function is given its own dynamics and naturally emerges nonminimally coupled to the gravitational field in a manner akin to teleparallel dark energy models or scalar-tensor theories in general relativity. New in the theory here presented, the cosmological function gives rise to a kinematic contribution in the deviation equation for the world lines of adjacent free-falling particles. While having its own dynamics, dark energy manifests itself in the local kinematics of spacetime.